The impact of institutionalization on the effectiveness of harm reduction: a qualitative study using drug users’ representations - Nicolas Khatmi; Lionel Dany; Perrine Roux (Harm Reduction Journal)
Abstract Context The French harm reduction (HR) model has been incorporated into health policies at the institutional level since 2004. To assess the effectiveness of this process, this article examines the representations of people who inject drugs (PWID) treated in care centers in France. In particular, it focuses on how they perceive themselves and their drug injection practices. Methodology We conducted a qualitative study using semi-structured interviews with 24 PWID attending both low- and high-threshold care centers. Lexical analysis and advanced statistical methods, including hierarchical clustering and correspondence analysis, were employed to elucidate the intricate relationships between the language utilized, the characteristics of the participants, and the care context. Results The analysis identified four lexical classes, which collectively represented 96.9% of the corpus. These were: economic aspects (C1), social relationships and stigma (C2), therapeutic and medical care (C3), and technical skills (C4) related to drug injection practices. Two principal factors of variability significantly influenced these classes. Factor 1 primarily distinguished the discourse of PWID according to their socio-economic status, forming a gradient from those in more precarious situations—who accessed low-threshold care centers—to those with greater social stability—who accessed high-threshold care centers. Factor 2 highlighted the influence of temporal markers on discourse, particularly the period of drug injection initiation. This factor reveals a pronounced contrast between participants who initiated injection prior to the 2000s and those who began during or after the 2000s. Conclusion Our results demonstrate that PWID’s experiences and perceptions were shaped not only by their socio-demographic characteristics but also by their social context, particularly the type of care center they attended. This study’s findings reveal the limitations of the institutionalized HR model in the French healthcare system and advocate the development of a community-based approach to HR that aligns with its original principles.